The effect of individual consciousness skills’ base counseling on sexual satisfaction of women at reproductivef age - Tayebe Ziaei; Marzieh Gorzin; Masumeh Rezai; Nasser Behnampour (Journal of Research Development in Nursing and Midwifery, 2018)
Introduction: Sexual satisfaction is an important indicator of sexual health and is strongly associated with satisfaction of interpersonal relationships. Self-awareness refers to pay attention to the thoughts, feelings, and it is the introduction of interpersonal relationships. Due to this relationship,a study was conducted to determine the impact of individual counseling based on self-awareness skills on sexual satisfaction in women of reproductive age of Gorgan, Iran. Methods: An interventional study was conducted as a field trial on 76 women of reproductive age referred to Gorgan health centers in the fall of 1395. The samples were availablility selected and randomly divided into intervention and control groups. In the first step, the Hudson Sexual Satisfaction Persian Questionnaire were completed by all women. Then,the women in the intervention group were consulted with six sessions of individual counseling based on self-awareness skills intervention. One month after counseling, both post-tests were performed in both groups.  Variables with T-student and Mann - Whitney using SPSS 16 software were analyzed. Results: There was no statistically significant difference between mean score of sexual satisfaction before intervention between two controls (103.21 ± 10.15) and intervention groups (102.36 ± 10.00). But, there was a statistically significant difference between mean score of sexual satisfaction after intervention; 103.39 ± 10.04 for the control group and 112.1 ± 7.97 for the intervention group (P-Value<0.0001). Conclusion: The results show that to increase sexual satisfaction promoting the awareness about sexual issues is not the only solution, but also promoting the self-awareness skills via recognizing their positive and negative characteristics is necessary. Hence, healthcare providers can use individual counseling based on self-awareness skills to increase sexual satisfaction.